1999
DOI: 10.1096/fasebj.13.14.1923
|View full text |Cite
|
Sign up to set email alerts
|

Local insulin‐like growth factor I expression induces physiologic, then pathologic, cardiac hypertrophy in transgenic mice

Abstract: In the present study we determined the long-term effects of persistent, local insulin-like growth factor I (IGF-I) expression on cardiac function in the SIS2 transgenic mouse. Cardiac mass/tibial length was increased in SIS2 mice by 10 wk of age; this cardiac hypertrophy became more pronounced later in life. Peak aortic outflow velocity, a correlate of cardiac output, was increased at 10 wk in SIS2 mice but was decreased at 52 wk. 72 wk SIS2 mouse hearts exhibited wide variability in the extent of cardiac hype… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
99
1
1

Year Published

2000
2000
2010
2010

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 148 publications
(105 citation statements)
references
References 23 publications
4
99
1
1
Order By: Relevance
“…This suggests a role for local IGF1 signalling, a notion that is supported by animal studies, showing that circulating IGF1 has little effect on overall growth in mice (10), while locally produced IGF1 is a prerequisite for GH-stimulatory effects in muscle and cartilage (51,52). IGF1 is known to induce collagen synthesis in animal tendon explants (39,40,53), and in mice that overexpress human IGF1 locally, it was demonstrated that the collagen content was elevated in heart muscle (54). These findings are in accordance with our results and support the view that IGF1, rather than GH, is directly responsible for the elevated collagen expression and protein synthesis seen in the present study.…”
Section: Systemic and Local Levels Of Igf1mentioning
confidence: 89%
“…This suggests a role for local IGF1 signalling, a notion that is supported by animal studies, showing that circulating IGF1 has little effect on overall growth in mice (10), while locally produced IGF1 is a prerequisite for GH-stimulatory effects in muscle and cartilage (51,52). IGF1 is known to induce collagen synthesis in animal tendon explants (39,40,53), and in mice that overexpress human IGF1 locally, it was demonstrated that the collagen content was elevated in heart muscle (54). These findings are in accordance with our results and support the view that IGF1, rather than GH, is directly responsible for the elevated collagen expression and protein synthesis seen in the present study.…”
Section: Systemic and Local Levels Of Igf1mentioning
confidence: 89%
“…Subsequent studies from the same group have demonstrated that IGF and PI 3-kinase activity are also involved in physiological hypertrophy of cardiomyocytes [28,29]. Another mouse model of cardiac IGF-1 overexpression has demonstrated that, while initially stimulating physiological cardiac hypertrophy, prolonged expression of IGF-1 in the heart progressively leads to a pathological hypertrophic condition [30]. IGF-1 and PI 3-kinase activation can protect primary cardiomyocytes from apoptosis [31,32], and IGF-1 signaling via PI 3-kinase and Akt has been shown to reduce cardiomyocyte apoptosis in vitro [33].…”
Section: Discussionmentioning
confidence: 99%
“…However, results of TG mouse studies in which IGF-I or IGF1R is overexpressed in the heart are somewhat conflicting. Overexpression of IGF-I in the heart using rat ␣-myosin heavy chain promoter results in myocyte proliferation (Reiss et al 1996), whereas ␣-skeletal actin promoter-mediated overexpression of IGF-I in cardiac and skeletal muscle induces physiological cardiac hypertrophy in the early phases of postnatal development and pathological hypertrophy in later phases (Delaughter et al 1999). IGF1R overexpression in the heart using mouse ␣-myosin heavy chain promoter results in physiological hypertrophy associated with increased myofiber size, enhanced contractile function, and activation of the PI3K-Akt-S6K pathway (McMullen et al 2004b).…”
Section: Insulin/igfmentioning
confidence: 99%